2018
DOI: 10.1186/s13256-018-1563-9
|View full text |Cite
|
Sign up to set email alerts
|

Rapid bupropion-induced hepatotoxicity: a case report and review of the literature

Abstract: We conclude that hepatotoxicity is a rare adverse effect of bupropion use, but physicians should be aware of the possibility of this potentially serious clinical picture of drug-induced hepatotoxicity with varied clinical presentation and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“… 45 In our study, bupropion had 38,648 reported adverse events, but no signals were detected in DILI. Based on the literature, we found less than 10 reported cases 46 of hepatotoxicity considered to be induced by bupropion. Hepatotoxicity may be a rare adverse effect; however, physicians should be aware that bupropion has caused a fatal case 47 of hepatotoxicity with autoimmune features.…”
Section: Discussionmentioning
confidence: 98%
“… 45 In our study, bupropion had 38,648 reported adverse events, but no signals were detected in DILI. Based on the literature, we found less than 10 reported cases 46 of hepatotoxicity considered to be induced by bupropion. Hepatotoxicity may be a rare adverse effect; however, physicians should be aware that bupropion has caused a fatal case 47 of hepatotoxicity with autoimmune features.…”
Section: Discussionmentioning
confidence: 98%
“…В нескольких случаях имели место иммуноаллергические проявления, выраженные в минимальной степени. Имеются сообщения о единичных случаях развития острой печеночной недостаточности с летальным исходом и хронического гепатита на фоне лечения обоими препаратами [16,19].…”
unclassified